„Cool bleiben”. Liebesdiskurse in der Literatur der Gegenwart. Überlegungen zu Romanen von Antje Rávic Strubel und Uwe Timm - Stephan, Inge (Studia Germanica Posnaniensia, 2015)
Metaphors of “coldness“ have increased dramatically in our present time, as evidenced by the three texts to be examined. The two novels Unter Schnee (2001) and Kältere Schichten der Luft (2007) by Antje Rávic Strubel focus on (or: are concerned with) lesbian relationships and the unfulfilled dreams through ties between the sexes. The novel Vogelweide (2013) by Uwe Timm runs through various heterosexual couple-constellations, for which the author utilizes the foil of Goethe’s Affective Affinities. He is con-scious of the fact that the traditional marriage has lost its status as a role model. All characters in the novel are searching for a new “language of love,” but in their pursuit they relapse to those clichés, which they sought to escape. ‘Heat’ and ‘coldness’ turn out to be metaphors that have become obsolete a long time ago. They now produce dichotomies and narrow the love-discourse to meteorological sensibilities. The strong presence of sensations of coldness in all three novels nevertheless is still revealing. It can be read as a Symptom – to stay with the metaphors of the texts – for a ‘cooling-down’ of the relationship between the sexes.